Code: Virals Series #3 - Reichs, Kathy; Reichs, Brendan (New York, NY : G. P. Putnam's Sons, 2013)
"The Virals must find a geocache concealing a bomb--and the clock is ticking."--
Keywords: Adventure and adventurers -- Fiction; Geocaching (Game) -- Fiction; Wolfdogs -- Fiction; Fathers and daughters -- Fiction; Single-parent families -- Fiction; Islands -- Fiction; Morris Island (S.C.) -- Fiction; Science fiction